Um estudo sobre os impactos de algumas medidas sanitárias na incidência e mortalidade por COVID-19 - Paiuta, Rhayani Aparecida (Universidade Federal de São Carlos, 2022)
Since March 2020, Brazil, like the whole world, has been facing a major pandemic caused by COVID-19 (SARS-CoV-2). COVID-19 is a highly transmissible respiratory infection and for this reason governments around the world have taken health measures to control cases of the disease and thus stop the pandemic. The lockdown was a sanitary measure used in some cities to prevent the movement of people on the streets and thus reduce the contamination of people with the disease. In addition, after almost a year since the beginning of the pandemic, some countries have started to apply vaccines as well in order to reduce the impacts of the pandemic. Faced with the uncertainty about what would actually be effective to control the number of cases and deaths from COVID-19, researchers and people of common sense began to be interested in these sanitary measures and began to question whether the lockdown or if the start of vaccination helped to control the pandemic. In this context, this work studied the effects of lockdown and vaccination on the number of new cases and the number of deaths by COVID-19 through time series techniques. After applying the methodology, we observed that the lockdown helped to reduce cases of COVID-19 in the city of Araraquara and that vaccination impacted the reduction of cases and deaths.
A study on the impacts of some health measures on the incidence and mortality of COVID-19
Keywords: Análise de intervenção; ARIMA; COVID-19; Suavização exponencial; Vacinação; Lockdown; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA EM PROCESSOS ESTOCASTICOS